Analisis Kejelasan Bahasa Hukum dalam Putusan Hakim di Pengadilan Negeri Gorontalo - Dali, Meilina Widya; Gino, Kikin Kinanti; Sana'u, Ariel. A.; Paputungan, Amelia Cahyani Putri; Rahman, Khairunnisa Pratiwi; Husain, Muh. Rizki Fauzan; Alhasni, Najwa Syifa; Hantulu, Revan Ramdan; Adham, Nazwa A. Bin; Abdul, Siti Ramadhani; Tuaru, Suci Rahmiyati; Nur, Sulistri M.; Lampeng, Wilanda Adela G.; Saerang, Nathanael Christian (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
This study analyzes the clarity of language in three judicial decisions of the Gorontalo District Court issued in 2023, 2024, and 2025 as part of the legal language register, which requires precision, consistency, and the absence of ambiguity. Legal language functions as a vital communication medium between judges and litigants; therefore, unclear sentence structures, ineffective phrasing, or overly detailed factual descriptions may weaken the normative strength of a decision. This study employs a qualitative descriptive method by examining the decisions’ sentence structure, discourse coherence, and relevance of information. The findings indicate that the 2025 decision demonstrates the lowest clarity due to lengthy sentences and irrelevant technical details. The 2024 decision provides moderate clarity with a more systematic structure despite some repetition. The 2023 decision is the clearest, featuring concise language and balanced separation between factual exposition and legal reasoning. The study highlights the need for simplified legal language to enhance readability and strengthen legal certainty.